High rate of seroeligibility among MYBPC3-associated hypertrophic cardiomyopathy patients for TN-201, an adeno-associated virus serotype 9 MYBPC3 gene therapy - Desai, Milind Y.; Massera, Daniele; Wang, Heng; Wong, Timothy C.; Wever-Pinzon, Omar; Lakdawala, Neal K.; Giudicessi, John R.; Abraham, Theodore; Nagueh, Sherif; Rader, Florian; Masri, Ahmad; Turer, Emre; et al. (Frontiers in Medicine, 2025)
BackgroundThe genetic etiology of hypertrophic cardiomyopathy (HCM) and the critical role of sarcomeric variants in its pathogenesis are well recognized (1). Among these, loss-of-function variants in the myosin binding protein C gene (MYBPC3) are the most prevalent, resulting in protein insufficiency when compared to healthy controls (1). Preclinical studies have shown that recombinant adeno-associated virus serotype 9 (rAAV9) carrying the full-length MYBPC3 transgene can increase protein expression and improve cardiac function. However, pre-existing anti-AAV9 antibodies—neutralizing (NAb) and total (TAb)—may limit gene transfer efficacy and eligibility for gene therapy. We sought to evaluate the prevalence of anti-AAV9 antibodies in patients with MYBPC3-associated HCM to optimize patient selection for MyPEAK-1, an ongoing trial evaluating the safety, tolerability, and pharmacodynamics of TN-201, an AAV9: MYBPC3 gene therapy.MethodsThis was a prospective, cross-sectional study of 100 adults (aged 18–65 years) with symptomatic MYBPC3-associated HCM (NYHA II–IV). Blood samples were analyzed for anti-AAV9 NAb (transduction inhibition assay) and TAb (electrochemiluminescence assay). Titers ≥1:10 were considered positive. Associations between antibody levels and demographic and clinical characteristics were explored using statistical tests.ResultsPre-existing anti-AAV9 NAb were undetectable in 50% of patients. Among those with detectable titers (range: 1:10–1:720), only 16% exceeded 1:40. TAb were undetectable in 53%; titers ranged from 1:10 to 1:65,600. A strong correlation was observed between NAb and TAb titers (r = 0.671, p < 0.001). Serostatus was not significantly associated with age, sex, NYHA class, or ethnicity (all p > 0.05).ConclusionPre-existing immunity to AAV9 was absent or low in most MYBPC3-associated HCM patients, with only a small proportion exceeding standard NAb thresholds for AAV gene therapy trials. These findings support the feasibility of a clinical trial of TN-201, an AAV9-based MYBPC3 gene replacement therapy, in this population. Given the concordance between NAb and TAb assays, either may be suitable for screening.